The NICE recommendation for drug-coated balloons and its global impact. (June 2015) - Eccleshall, Simon; Waliszewski, M.
Objectives: The clinical efficacy and safety of drug-coated balloon (DCB) angioplasty in patients with coronary in-stent restenosis (ISR) has been demonstrated. The objective of this article is to provide comparative cost efficacy data for DCB angioplasty in various countries based on the original methodology of the Medical Technologies Evaluation Programme (MTEP) at the National Institute for Health and Clinical Excellence (NICE) in 2010. Study design: Published and unpublished Health Technology Assessment (HTA) reports were evaluated for comparison in selected countries. Furthermore, a systematic review of economic evaluations of DCB angioplasty versus standard treatments (uncoated balloon angioplasty or drug-eluting stent implantations) was conducted. Methods: National cost efficacy data were evaluated using Markov state transition models which were adapted to fit each country's device and procedure related costs. The clinical input for adverse events was defined with two relevant trials for in-stent restenosis of bare metal stents (BMS-ISR) and of drug-eluting stents (DES-ISR). Results: In the UK, Germany, Switzerland, South Africa, Japan and Brazil, DCB angioplasty is cost-effective when compared with drug-eluting stents to treat either BMS-ISR or DES-ISR. Conclusions: DCB angioplasty ought to be the preferred treatment option for patients with BMS-ISR and DES-ISR from the payers' point of view.